Local Wisdom Housing Governance Balances Sustainability and Legal Certainty: Kebijaksanaan Lokal dalam Tata Kelola Perumahan Menyeimbangkan Keberlanjutan dan Kepastian Hukum - Arna, Md. Andhi Supriatna; Padmawati, Ida Ayu Putu Sri Astiti (Academia Open, 2026)
General Background: Housing governance increasingly faces tensions between rapid property investment and the preservation of socio-cultural and environmental values. Specific Background: The expansion of commercial housing development has introduced external values that gradually erode local wisdom embedded in traditional settlement systems, while existing regulatory frameworks remain outdated and fragmented. Knowledge Gap: There is an absence of comprehensive and operational legal instruments that explicitly integrate local wisdom into housing governance, resulting in juridical uncertainty, sociocultural degradation, and philosophical inconsistency. Aims: This study examines the nature of local wisdom-based housing governance, evaluates current regulatory conditions, and formulates an ideal regulatory model grounded in sustainable development principles. Results: Findings indicate that local wisdom-based governance embodies a holistic system integrating social, economic, environmental, and spiritual dimensions, rooted in the philosophy of Tri Hita Karana; however, existing regulations fail to adequately protect these values and lack technical implementation mechanisms. The proposed model emphasizes regulatory revision, establishment of new legal frameworks, and formal recognition of customary institutions in licensing and supervision. Novelty: This study introduces a comprehensive legal construction that systematically embeds cultural values into housing governance through normative integration and institutional alignment. Implications: The model provides a strategic framework for achieving balanced development, reinforcing cultural identity, ensuring legal certainty, and promoting sustainable housing governance across generations. Highlights: Holistic integration of cultural, environmental, and social dimensions forms the core governance structure. Regulatory fragmentation generates legal uncertainty and accelerates cultural degradation. Institutional alignment with customary systems establishes a structured and sustainable policy framework. Keywords: Housing Governance, Local Wisdom, Traditional Balinese Architecture, Sustainable Development, Legal Norm Vacuum.